Predictors of recidivism over 3 years among substance-using women released from jail - Scott, Christy K. (Criminal justice and behavior, 2014)
This study examines predictors of recidivism over 3 years for 624 women released from a county jail using a comprehensive range of standardized measures derived from gender-responsive and gender-neutral criminogenic recidivism models. Although more than a dozen factors were related to recidivism in the univariate analysis, the multivariate analysis shows that recidivism can be reliably predicted (area under the curve = 0.90) with just four factors: age, no custody of children, substance use frequency, and number of substance problems. Exploratory analysis of women who recidivated in post-release months 1 to 3, 4 to 12, and 13 to 36 revealed that the effects of several variables (age, super optimism, and number of weeks in the jail treatment program) were dependent on the time elapsed since release from jail, whereas others (substance use and custody) had persistent effects over time. These findings support the development of re-entry services tailored for female offenders who address both gender-responsive and gender-neutral criminogenic risk factors.